Analysis of blood donors’ characteristics during third-peak COVID-19 in Bojonegoro Regency, Indonesia - siti - nurkasanah (Journal of Community Empowerment for Health, 2023)
The third peak of the Coronavirus Disease 2019 (COVID-19) in Indonesia which was recorded on February-March 2022 had an impact on voluntary blood donations at the Indonesian Red Cross (IRCS) Bojonegoro. The objective of this research was to analyze the voluntary blood donors’ characteristics during the third COVID-19 peak in Bojonegoro Regency. This descriptive, analytical study was conducted using secondary blood donor data from February 22, 2022 to March 19, 2022 at IRCS Bojonegoro. The data were collected in the blood donor selection process in accordance with the Indonesian and World Health Organization (WHO) blood donor selection guidelines. The average number of voluntary blood donors per day was tested using the Mann-Whitney-U test with a significance ofp<0.05. The results showed 219 people (80.51%) between 22-28 February and 332 people (83.63%) between 1-19 March 2022 who were approved to donate at IRCS Bojonegoro. There was a significant decrease in the average of male voluntary blood donors per day (p=0.01),average age group: 17-24 years (p=0.013), 35-44 years (p=0.002), and 45-54 years (p=0.030), hemoglobin (Hbl) levels on 16.1-17.0 g/dL (p=0.000), systolic blood pressure (SBP) <120 (p=0.03) and 130-139 (p= 0.02) and diastolic blood pressure (DBP) <80 (p=0.001), pulse rate (PR) 65-74 beats/minute (p=0.016), and blood type O+ (p=0.008). The characteristics of voluntary blood donors during the third peak of COVID-19 in Bojonegoro Regency indicated there was a significantly decreased number of male voluntary blood donors per day around ages 17-24 and 35-54 years, with Hbl between 16.1-17.0 g/dL, SBP <120 and 130-139 mmHg, DBP <80 mmHg, PR 65-74 beats/minute, body weight 45-54 and 65-74 kg, and blood type O+.